2021
DOI: 10.17660/actahortic.2021.1309.124
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry postharvest shelf life is related to total acid content and fruit firmness

Abstract: Strawberry fruit has a short post-harvest shelf life because it is very perishable and susceptible to several pathogens that quickly reduce the quality of the fruit. A large part of Huelva's strawberry production is exported, so the shelf life of the fruit is one of the main factors that determines the quality of the fruit when it reaches its destination. The aim of this work was to explore the relationship between postharvest shelf life and the agronomic and quality traits in different strawberry genotypes du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…There are studies showing penetrometer measurement correlation with texture attributes [12]. Penetrometers are usually used for determining the texture and firmness of fruits, [12,13] but some studies have also shown the use of penetrometers, which should provide objective data compared to tasters, to determine the toughness and texture of the leaves. Takeuchi and Zalucki [16] used a penetrometer to determine Eucalyptus leaf toughness; Wang et al [17] and Salgado-Luarte et al [18] measured the leaf toughness of different spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies showing penetrometer measurement correlation with texture attributes [12]. Penetrometers are usually used for determining the texture and firmness of fruits, [12,13] but some studies have also shown the use of penetrometers, which should provide objective data compared to tasters, to determine the toughness and texture of the leaves. Takeuchi and Zalucki [16] used a penetrometer to determine Eucalyptus leaf toughness; Wang et al [17] and Salgado-Luarte et al [18] measured the leaf toughness of different spp.…”
Section: Discussionmentioning
confidence: 99%
“…The force required by the metallic tip to penetrate a microgreen leaflet was recorded. The penetrometer is usually used to determine the texture of fruits, for example, apples and strawberries [12,13]. However, some studies have also shown the use of a penetrometer to determine the toughness and texture of the leaves [15][16][17][18][19].…”
Section: Determination Of Leaf Texture/toughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…During ripening, in addition to developing in colour and anthocyanin content, strawberries become softer [12,16]. This makes them more difficult to transport, because softer fruits are more likely to be damaged, and have a shorter shelf life [17,18]. In order to maximise shelf life, strawberries for the fresh market are typically harvested before they have fully developed to their peak colour and anthocyanin content, and consequently are not at the optimal ripeness to produce nectars with the most stable colour.…”
Section: Introductionmentioning
confidence: 99%